1995
DOI: 10.1111/j.1365-2249.1995.tb03864.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tetracyclines on T cell activation

Abstract: SUMMARYMinocycHne has been shown to have an anti-inflammatory effect in patients with rhetimatoid arthritis (RA). Since there is evidence thai RA is a T cell-mediated disease, we investigated Ihe efl'ect of minocycline on human T cell clones derived from the synovium of an RA patient. The T cells, when activated via the T cell receptor {TCR)/CD3 complex, were suppressed functioniiUy by minocyciine, resulting in a dose-dependent inhibition of T eell proliferation and reduction in production of lL-2. inlerferon-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 27 publications
(29 reference statements)
4
45
0
1
Order By: Relevance
“…In vitro studies have revealed that minocycline inhibited antigen processing for presentation to human T-cells (Kalish and Koujak, 2004), T-cell proliferation and production of inflammatory cytokines (Kloppenburg et al, 1995;, and T-cell transmigration across a fibronectin matrix barrier, most likely via the inhibition of MMPs. In vivo assays have found that this antibiotic promotes immune differentiation from a type 1 helper T-cell (Th1) to a type 2 helper T-cell (Th2) phenotype, thus modulating the susceptibility to EAE (Popovic et al, 2002).…”
Section: Effects Of Minocycline On Cns Pathologiesmentioning
confidence: 99%
“…In vitro studies have revealed that minocycline inhibited antigen processing for presentation to human T-cells (Kalish and Koujak, 2004), T-cell proliferation and production of inflammatory cytokines (Kloppenburg et al, 1995;, and T-cell transmigration across a fibronectin matrix barrier, most likely via the inhibition of MMPs. In vivo assays have found that this antibiotic promotes immune differentiation from a type 1 helper T-cell (Th1) to a type 2 helper T-cell (Th2) phenotype, thus modulating the susceptibility to EAE (Popovic et al, 2002).…”
Section: Effects Of Minocycline On Cns Pathologiesmentioning
confidence: 99%
“…Multiple immunosuppressive agents target NFAT activation by acting on the phosphatase calcineurin, preventing binding and activation by the Ca 2Ï© -dependent protein calmodulin (25). It has been suggested that the ability of minocycline to suppress T cell proliferation may be related to chelation of Ca 2Ï© , but others were unable to demonstrate that minocycline altered intracellular Ca 2Ï© concentrations (10). We utilized an in vitro phosphatase assay to determine whether the effects of minocycline on NFAT dephosphorylation could be explained by direct chelation of available Ca 2Ï© reducing calcineurin activity or a direct interaction between minocycline and calcineurin, thereby inhibiting its activity (Fig.…”
Section: Minocycline Reduces Transcriptional Activity Of Nfat-mentioning
confidence: 99%
“…In rheumatoid arthritis patients, minocycline significantly improved clinical symptoms and increased the frequency of remissions leading to its usage as a disease modifying anti-rheumatic drug (7)(8)(9). Studies using CD4 Ï© T cell clones derived from the synovium of an rheumatoid arthritis patient showed that minocycline decreased activation-induced proliferation and inflammatory cytokine production (10). Minocycline has also shown therapeutic effects on T cells in experimental autoimmune encephalomyelitis, an animal model of multiple sclerosis.…”
mentioning
confidence: 99%
“…There are many similarities between the administration of minocycline or anti-EMMPRIN Abs in their ability to modulate T cell activities (1,29,49,50). For example, both minocycline and anti-EMMPRIN Abs reduced T cell proliferation (5,6,12,51,52).…”
Section: Discussionmentioning
confidence: 99%